Home parenteral nutrition‐associated thromboembolic and bleeding events: results of a cohort study of 236 individuals. (13th June 2016) - Barco, S.; Heuschen, C. B. B. C. M.; Salman, B.; Brekelmans, M. P. A.; Serlie, M. J.; Middeldorp, S.; Coppens, M.
Abstract : Essentials Sparse or outdated studies focus on thrombotic and bleeding risk in home parenteral nutrition (HPN). 236 HPN patients followed at a single center for a total of 684 patient‐years were evaluated. Rates of venous thrombosis and major bleeding, and prevalence of vena cava syndrome are provided. Anticoagulants might reduce thrombosis risk, but population‐specific safety concerns remain. Summary: Background: Home parenteral nutrition (HPN) is necessary for patients with intestinal failure. Recurrent catheter‐related thrombosis (CRT) is common, leading to infectious complications, pulmonary embolism, vascular access loss and intestinal transplantation. The efficacy and safety of anticoagulants are unknown in this setting and based on sparse and low‐quality observational data. Objectives: Our aim was to estimate the incidence of thromboembolic, bleeding and anticoagulant‐related complications in HPN patients, and evaluate risk factors for first venous thrombosis (VT). Methods: This retrospective cohort study included all adult patients followed for long‐term HPN at our center between 1986 and 2014. Primary outcomes were symptomatic objectively diagnosed VT, encompassing CRT and venous thromboembolism, and major bleeding. Secondary outcomes were vena cava syndrome and heparin‐induced thrombocytopenia or hypersensitivity. Results: A total of 236 patients were included (median HPN duration, 17 months) and 136 received anticoagulants at HPN onset (57.6%). Overall, the annual incidence of first VT was 11.4% (95% confidence interval [95% CI], 8.6–14.7%); VT was associated with a personal history of thrombosis (adjusted hazard ratio, 2.22; 95% CI, 1.06–4.64), whereas anticoagulation seemed to account only for a mild protection (adjusted hazard ratio, 0.72; 95% CI, 0.36–1.44). The annual incidence of major bleeding was 4.3% for patients on anticoagulants vs. 1.8% for those off anticoagulants. Vena cava syndrome developed in 20.7% of patients with VT. One patient had isolated heparin‐induced thrombocytopenia (0.6%) and four had heparin hypersensitivity (2.5%). Conclusions: Patients on HPN have a significant risk of venous thrombosis, major bleeding and vena cava syndrome. Anticoagulants might reduce thrombosis risk, but population‐specific safety concerns remain.